A biophoton method for identifying the quality states of fresh Chinese herbs - Cao, Baorui; Wang, Zhiying; Zhang, Jiayi; Fu, Jialei; Zhang, Zhongwen; Du, Jinxin; Deng, Tingting; Pang, Jingxiang; Yang, Meina; Han, Jinxiang (Frontiers in Pharmacology, 2023)
Introduction: The quality of Chinese herbs is the basis for ensuring their safety and efficacy. However, the quality evaluation system is imperfect. In particular, there is a lack of quality evaluation methods for fresh Chinese herbs during growth. The biophoton is a common phenomenon and provides complete information about the interior of the living system, which is consistent with the holistic concept of traditional Chinese medicine. Therefore, we aim to correlate the biophoton characteristics with the quality states to find the biophoton parameters that can characterize the quality states of fresh Chinese herbs. Methods: The biophoton characteristics of motherwort and safflower were measured and characterized by the counts per second (CPS) in the steady state and the initial intensity (I0) and coherent time (T) of delayed luminescence. The active ingredient content was measured by ultra-high-performance liquid chromatography (UPLC). The pigment content of motherwort leaves was measured by UV spectrophotometry. The t-test and correlation analysis were performed on the experimental results. Results: The CPS and I0 of motherwort and I0 of safflower showed a significant downward trend during the growth process, and their active ingredient content showed a trend that increased and then decreased. The CPS, I0, and the content of active ingredients and pigments in a healthy state were significantly higher than those in a poor state, while T showed the opposite results. The CPS and I0 were all significantly and positively correlated with the content of active ingredients and pigments, while the T of motherwort showed the opposite results. Conclusions: It is feasible to identify the quality states of fresh Chinese herbs by using their biophoton characteristics. Both CPS and I0 have better correlations with the quality states and can be considered characteristic parameters of the quality of fresh Chinese herbs.